Empowering the user with contextual information: from location infrastructures to augmented reality interfaces - Danado, José Carlos dos Santos (2007)
Sumário - O trabalho apresentado nesta dissertação envolve a utilização de realidade aumentada como uma interface ubíqua no mundo real. A tese discute ainda diferentes aspectos associados aos diferentes módulos necessarios para o desenvolvimento de um sistema de computação ubíqua, nomeadamente a aquisição de contexto e a apresentação de informação ao utilizador. No contexto da tese, são ainda discutidas novas arquitecturas, métodos e técnicas para melhorar os sistemas de computação ubíqua. Esta secção apresenta uma breve descrição da tese, assim como as questões e objectivos que levaram à sua realização. ### Summary - Augmented Reality and Ubiquitous Computing are evolving topics in computer science. In this dissertation, augmented reality is discussed as a ubiquitous interface applied to several events in the real world, namely environmental management, every day's life and entertainment. Throughout the dissertation, different aspects of the development of augmented reality systems for ubiquitous computing are presented, such as a number of architectures, methods and techniques to ubiquitously locate persons and objects and visualize related information. There are several technologies used to track persons and object, however their capabilities and limitations make each technology more suitable for specific purposes. One example is the limitation presented by GPS, used to track users or objects outdoor.